High-performance human resource practices, organizational identification and employee commitment: the moderating role of organizational culture - Yang, Yifan; Mostafa, Ahmed Mohammed Sayed (Frontiers in Psychology, 2024)
Purpose Drawing on social exchange and social identity theories, this study examines the mediating role of organizational identification on the relationship between high-performance human resource practices (HPHRPs) and employee commitment. The study further examines the moderating role of organizational culture in this mediated relationship. Method A cross-sectional survey was conducted with 340 employees from state-owned enterprises in China, and SPSS was used to test the hypothesized relationships. Findings The results indicate that organizational identification acts as a mediator of the relationship between HPHRPs and employee commitment. Additionally, organizational culture moderates the strength of this mediated relationship, affecting the degree to which HPHRPs foster commitment. Originality This study contributes to the literature by integrating social exchange and social identity theories to explain the psychological mechanisms underlying the employee-organization relationship. It also extends the understanding of how organizational identification mediates the link between HPHRPs and commitment, and how organizational culture moderates these effects, providing a more comprehensive understanding of these interrelated dynamics in organizational settings.